Los egresados y la calidad de la educación superior:una visión desde las encuestas a graduados (2006)
This article presents the usefulness of researches on university graduates in processes of quality assessment in universities and programs. It recognizes the lack of unanimity about the validity of survey results in order to verify the education quality and shows the importance of some statistical tests to verify the relationships between the graduate’s answers. Some relevant results from surveys on graduates from Universidad EAFIT (Medellín) and Universidad de La Sabana (Bogotá), applied in 2002 and 2004, are displayed.